Suckling behaviour of Nelore, Gir and Caracu calves and their crosses - Rodrigues Paranhos da Costa, Mateus Jose; Albuquerque, Lucia Galvao; Eler, Joanir Pereira; de Vasconcelos Silva, Josineudson Augusto (Elsevier B.V., 2006)
It is reasonable to assume that the knowledge of suckling behaviour contributes to optimal management and selection of beef cattle. However, there is little information about suckling behaviour of some beef cattle breeds. The aim of this study was to describe the suckling behaviour of two zebu (Bos indicus) and one criollo (Bos taurus) breeds, analysing the potential effects of breed and some environmental factors on suckling frequency and duration. Forty cows, 17 Nelore, 14 Gir (both zebu) and 9 Caracu (criollo) were bred in a diallelic crossing design. The cows and resulting calves were kept on pasture from birth to weaning. Their behaviour was recorded weekly during daylight. Three behavioural traits were considered: number of suckling meals (NSM), duration of each suckling meal (DSM) and total suckling duration (TSD). Allosuckling was not observed. The calves suckled at any time during the daylight and the overall means were: NSM = 2.57 +/- 0.05 meals/12 h (from back transformed data), DSM = 9.25 +/- 0.11 min/suckling meal and TSD = 23.76 +/- 0.47 min/12 h. There was an effect of dam's breed on NSM and DSM; the calf's genetic group within breed of cow influenced NSM and TSD when the dams were from the Nelore breed. The age of calf had significant effects on all traits. Males averaged higher NSM and TSD (2.60 +/- 0.03 meals and 25.05 +/- 1.37 min/12 h, respectively) than females (2.12 +/- 0.04 meals and 21.51 +/- 1.55 min/12 h, respectively). The differences in suckling behaviour seem to be produced by a complex combination of genetic and environmental factors, which result in a particular behavioural relationship within mother-offspring pairs. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Cattle; cow-calf relationship; milk transfer estimation; breed differences; suckling